Perancangan Turbin Angin Horizontal Pada Mobil Hybrid - Alex Surapati; Vikriandi Tri Putra (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Scarcity of energy in the form of fossil fuels in the spotlight, the whole world began to look for solutions about the rescue. The best alternative is use renewable energy, which comes from nature that can be directly utilized freely and without limits such as wind energy. Utilization of wind energy can be applied to human needs, for example for energy sources for electric cars. This rescarch aims to design a wind turbine to help charge batteries in hybrid cars (wind power and solar power). The research method starts from the design of tools, testing tools and analyzing the results of measurements, Power from wind power. into electrical energy using 3 blades with a blade diameter of f 60 cm (r-30 cm) and has a width of 4 cm which is placed horizontally with aheight of 136 cm from the ground and placed on the front side of the car. The results obtained in this study are the wind speed of 4.5 m/s can produce a maximum rotation of the wind turbine of 782 rpm and produce a voltage of 4.05 volts, a current of 0.23 Amperes, and a power of 0.9315 Walt. The generator in a wind turbine has a maximum output power of 0.27 Watt with an average output voltage of 1.8 volts and an average current of 0.15 Amperes.